52.3k views
5 votes
Solve 3[-x+(2x+1)]=x-1

User Postsrc
by
4.9k points

1 Answer

4 votes

Answer:

x=-2

Explanation:

First, we can use the distributive property on the left side to give us

-3x+3(2x+1)=x-1

Distributing a second time gives us

-3x+6x+3=x-1

Simplifying the left side gives us

3x+3=x-1

Next, we can subtract x from both sides, giving us

2x+3=-1

Then, we can subtract 3 from both sides, resulting in

2x=-4

Lastly, dividing both sides by 2 gives us

x=-2

User Morgler
by
5.2k points